2011
DOI: 10.1364/oe.19.015415
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative imaging of cochlear soft tissues in wild-type and hearing-impaired transgenic mice by spectral domain optical coherence tomography

Abstract: Human hearing loss often occurs as a result of damage or malformations to the functional soft tissues within the cochlea, but these changes are not appreciable with current medical imaging modalities. We sought to determine whether optical coherence tomography (OCT) could assess the soft tissue structures relevant to hearing using mouse models. We imaged excised cochleae with an altered tectorial membrane and during normal development. The soft tissue structures and expected anatomical variations were visible … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
35
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
2
1

Relationship

4
5

Authors

Journals

citations
Cited by 49 publications
(35 citation statements)
references
References 35 publications
0
35
0
Order By: Relevance
“…Previously, we described our spectral domain OCT system for in vitro cochlear imaging [13]. We have now modified it to improve our ability to collect in vivo vibrometric data.…”
Section: Oct System Descriptionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previously, we described our spectral domain OCT system for in vitro cochlear imaging [13]. We have now modified it to improve our ability to collect in vivo vibrometric data.…”
Section: Oct System Descriptionmentioning
confidence: 99%
“…Previous OCT imaging experiments by our lab and others have shown it to be effective in resolving soft tissues within the cochlea, including the various substructures that compose the organ of Corti [13][14][15][16]. Vibration measurements have been made using OCT within the opened guinea pig cochlea in vivo [17,18].…”
Section: Introductionmentioning
confidence: 99%
“…However, some recordings have been made from the top surface of the organ of Corti in the guinea pig cochlear apex using LDV (12)(13)(14). More recently, optical coherence tomography (OCT) has been used to study how regions within the organ of Corti other than the BM vibrate because it permits depth-resolved measurements inside tissue (15)(16)(17)(18). These data have indicated that this complex structure does not vibrate as a rigid body (19,20).…”
mentioning
confidence: 99%
“…The novel improvements in imaging technologies resulted in the introduction of experimental imaging modalities to evaluate the intracochlear microanatomy such as OCT and SLOT (7,(11)(12)(13)(14). These high resolution modalities are nondestructive and facilitate near real time evaluation of the structures.…”
Section: Discussionmentioning
confidence: 99%